2017
DOI: 10.18203/2394-6040.ijcmph20171352
|View full text |Cite
|
Sign up to set email alerts
|

Childhood diarrhoea: assessment of knowledge, attitude and practices among mothers attending the tertiary care hospital - an observational analytical study

Abstract: Background: Diarrhoea is a major killer of children under-five, accounting for about 8% of deaths. For children aged under-five years, a median of three episodes of diarrhea occur per child-year. Assessment of knowledge, attitude and practice of mothers of under-five children.Methods: All mothers of under-five years who attended out-patient department of Pediatrics within the study period were interviewed. A total 200 mothers were assessed regarding the knowledge, attitude and practices towards childhood diarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In a study done among mothers in a tertiary care hospital it was found that 11.5% of the mothers were illiterate, 51.5% had studied up to high school level and 12.5% were graduates or post-graduates. 8 In the present study 90.2% of the mothers were housewives and rest (9.8%) were employed.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In a study done among mothers in a tertiary care hospital it was found that 11.5% of the mothers were illiterate, 51.5% had studied up to high school level and 12.5% were graduates or post-graduates. 8 In the present study 90.2% of the mothers were housewives and rest (9.8%) were employed.…”
Section: Discussionmentioning
confidence: 44%
“…Similarly in another study 58.5% mothers continued to feed their child, while 26% fed their child to some extent and remaining 15.5% stopped to feed. 8 Preventive measures known to the mothers were boiling /treating drinking water (63.2%), maintaining personal hygiene (65.7%), eating fresh food (72.3%). In another study 62% mothers perceived the importance of personal hygiene and very few mothers (14.5%) knew about boiling water as a preventive method.…”
Section: Discussionmentioning
confidence: 99%
“…[9,18] Although most childhood diarrhoea episodes are mild, acute episodes can result in severe loss of fluids and dehydration, leading to severe health-related consequences and death. [19] Diarrhoeal disease can be prevented simply by properly washing hands, feeding and immunisation. Acute diarrhoea can also be treated with oral rehydration and zinc.…”
Section: Discussionmentioning
confidence: 99%
“…In consistent with our findings, many studies reported a low level of mothers towards causes and transmission of diarrhea. [ 2 , 17 , 23 ]. A study from Nigeria reported that the most common causes for childhood diarrhea were contaminated food (24.1%) and unclean water (11.3%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%